Apakah Cost Plus Pricing Masih Relevan Di Masa Covid19 - Hartanti, Rina (Fakultas Ekonom dan Bisnis, Universitas Tarumanagara, 2020)
Objective of this study to analyze effect of cost plus pricing method on the increase or decrease in company profits. This research is also aimed at analyzing the concept of calculating the selling price of foreign tour products. Data was obtained by conducting direct interviews and distributing 150 questionnaires to frontline employees at Travel Agentun Jakarta. From 150 questionnaires shared to participants, only 138 were successfully filled in and processed, then analyzed using Structural Equation Models (SEM). The findings of the research are :the use of cost plus pricing method in calculating selling price of foreign tour products affects the decline in company profits so that it is irrelevant as the basis for strategic decision making of travel agencies in Jakarta, due to the difficulty in achieving the minimum number of tour participants and the profit margin limit. required, especially during the Covid pandemic 19. The research implication is that the cost plus pricing method may be irrelevant if it fails to meet minimum requirements for Â number of tour participants and profit margin.